Pattern of Presentation of Headache among Attendees of Health Centres Attached to a Tertiary Care Hospital, Dharwad - Prajna Sharma; Lata R Kollur (Medsci Publications, 2017)
Introduction: Despite that headache is felt, at some time, by nearly everybody, it is not known how, or how many of the populations of the world, or how healthcare and other resources are utilized to mitigate their effects. Globally, it has been estimated that prevalence among adults of current headache disorder is 47% in general. This study was conducted to know the pattern, factors triggering and associated with headache. Materials and methods: A time bound cross-sectional study was conducted for a period of two months. Using convenient sampling individuals10 years and above and had at least one episode of headache in last one month were interviewed. Results: Mean age presenting with headache was 29.26 +/- 12.13 years. Predominant age at onset was <20 years (55.7%). Monthly frequency (47.54%), bilateral location of headache (54.1%) and throbbing nature (59.01%) were more common. Most common triggering factors were sleep disturbance (63.9%) and stress (55.7%). Worsening was seen by any form of exertion (32.8%) and relieving factors included medication (54.1%) and rest (41%). Conclusion: Headache mainly affects the working population (18-40yrs) which reduces their working efficiency. Hence measures have to be taken to prevent and reduce the frequency of headache.